Dihydromyricetin Reduced Bcl-2 Expression via p53 in Human Hepatoma HepG2 Cells - Wu, Shixing; Liu, Bin; Zhang, Qingyu; Liu, Jie; Zhou, Wei; Wang, Chang; Li, Mingyi; Bao, Shiting; Zhu, Runzhi (PloS one, 2013)
Dihydromyricetin (DHM) is a major active ingredient of flavonoids compounds. It exhibited anticancer activity and induced apoptosis in human hepatocellular carcinoma HepG2 cells according to our previous data. In this study, we investigated whether p53 is involved in DHM-triggered viability inhibition and apoptosis induction in cancer cells. MTT [3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide] assay was employed to evaluate the viability of HepG2 cells after DHM treatment. Meanwhile, p53 small interfering RNA (siRNA) was adopted to silence p53 expression. Protein level of p53 and Bax/Bcl-2 were evaluated by western blot analysis. Cell counting assay showed that DHM inhibited HepG2 cell growth effectively in a time- and dose-dependent manner. P53 expression was significantly increased after DHM treatment, whereas Bcl-2 was reduced potently. Furthermore, after co-treatment with Pifithrin-α (PFT-α, p53 inhibitor), Bcl-2 expression was reversed. The expression of Bax was no significant change, which was also observed after p53 silence. These findings defined and supported a novel function that DHM could induce human hepatocellular carcinoma HepG2 cells apoptosis by up-regulating Bax/Bcl-2 expression via p53 signal pathway.